2022
DOI: 10.1093/nar/gkac1135
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of siRNA selection by plant Argonaute proteins triggering DNA methylation

Abstract: The model plant Arabidopsis thaliana encodes as many as ten Argonaute proteins (AGO1–10) with different functions. Each AGO selectively loads a set of small RNAs by recognizing their length and 5′ nucleotide identity to properly regulate target genes. Previous studies showed that AGO4 and AGO6, key factors in DNA methylation, incorporate 24-nt small-interfering RNAs with 5′ adenine (24A siRNAs). However, it has been unclear how these AGOs specifically load 24A siRNAs. Here, we biochemically investigated the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…This duplex had mismatches at positions 5, 9, and 16 to enhance passenger strand ejection. It should be noted that although this duplex lacks a mismatch at position 1, the guide strand selection is preferentially biased, as one strand’s 5′ terminal base is A while the other strand’s is G, as described by Liu et al, 2022 (44).…”
Section: Methodsmentioning
confidence: 85%
“…This duplex had mismatches at positions 5, 9, and 16 to enhance passenger strand ejection. It should be noted that although this duplex lacks a mismatch at position 1, the guide strand selection is preferentially biased, as one strand’s 5′ terminal base is A while the other strand’s is G, as described by Liu et al, 2022 (44).…”
Section: Methodsmentioning
confidence: 85%
“…Previously, studies have been undertaken concerning the structure of the MID domain of Argonaute proteins, highlighting its responsibility for the selective recognition of the 5′ nucleotide (Frank et al 2012 ). Interestingly, a coordination between the MID and PIWI domains has been identified as the underlying reason for this specificity (Liu et al 2022 ). In our study, we found that, among the conserved sites involved in 5′ nucleotide anchoring, only one site differed between AtAGO4, HvAGO4A and HvAGO4B, which was conserved between rice and barley (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in Arabidopsis , AGO6 was found to be able to load 24-nt sRNAs, as well as shorter sRNAs (19–22 nt), but with an exclusive preference for sRNAs with A residues at their 5′ ends. These length- and nucleotide-specific features ensure non-competition with other AGO proteins, particularly AGO1, which primarily binds miRNAs characterized by a length of 21 nucleotides and a starting base of U (McCue et al 2015 ; Liu et al 2022 ). This diversification might play a more specialized role in barley and tissues where both AGO4 proteins are expressed, potentially involving distinct localizations at the cell type level between the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Pol IV transcribes these regions producing short single-stranded RNAs (ssRNAs), which are then converted into double-stranded RNAs (dsRNAs) by the RNA-directed RNA polymerase 2 (RDR2) [ 31 ]. These dsRNAs are cleaved by the endoribonuclease enzyme DCL3 into 24-nucleotide small interfering RNAs (siRNAs) and are loaded onto Argonaute 4 (AGO4) or AGO6 proteins forming an AGO–siRNA duplex that enables AGO proteins to recognize and bind to RNA sequences complementary to the siRNA partner [ 32 ]. The second stage of this pathway involves the recruitment of Pol V to chromatin by DNA methyl readers SUVH2 and SUVH9 together with the DDR complex (consisting of DMS3, DRD1, and RDM1), leading to the synthesis of Pol V non-coding transcripts [ 33 , 34 ].…”
Section: Overview Of Epigenetic Mechanisms In Plantsmentioning
confidence: 99%